The road to drink is paved with high intentions: Expectancies, refusal self-efficacy, and intentions among heavy drinking college students - Foster, Dawn W. (Alcohol, 2015)
BACKGROUND: The present study examined the effects of drinking intentions (DI) on alcohol expectancies (AE) and drink refusal self-efficacy (DRSE) in regards to alcohol consumption among heavy drinking undergraduates. Research shows that DRSE buffers against drinking (Young et al., 2007) and interacts with AE to predict alcohol consumption (Oei & Burrow, 2000). Studies further show that DI is predicted by DRSE (Norman, 2011) and AE (Fleming et al., 2004). However, additional research is needed to understand DI’s influence on both DRSE and AE among heavy college drinkers. METHOD: This research included 344 heavy drinking college students (M age = 23.06, SD = 5.61, 74.71% female) from a large southern university who completed study material as part of a larger intervention. RESULTS: Findings showed that DI, DRSE, and AE interacted with respect to heavy drinking such that DRSE was negatively associated with alcohol consumption, particularly among those low in positive AE and high in negative AE. This relationship was stronger among individuals low in DI relative to those high in DI. DISCUSSION: DI seems to be an important factor influencing heavy drinking among undergraduate students. Present findings further support DI’s associations with heavy drinking, regardless of an individual’s DRSE or AE. Implications of this research suggest that it may be beneficial for interventions to target specific aspects of AE, including anxious drinking.